2017
DOI: 10.1002/psc.2992
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction of the optimal oligomeric state for membrane‐inserted β‐barrels of protegrin‐1 and related mutants

Abstract: Protegrin-1 is a widely studied 18-residue β-hairpin antimicrobial peptide. Evidence suggests that it acts via a β-barrel pore formation mechanism, but the exact number of peptides comprising the pore state is unknown. In this study, we performed molecular dynamics simulations of β-barrels of protegrin and three related mutants (v14v16l, v14v16a, and r4n) in NCNC parallel topology in implicit membrane pores of varying radius and curvature for oligomeric numbers 6–14. We then identified the optimal pore radius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
(80 reference statements)
1
13
0
Order By: Relevance
“…Similar distortions of β-sheet conformations were reported in other simulations studies of PG-1 in water or in the presence of micelles but were not related to possible issues with the ability of the force field to describe correctly the conformation of the peptide [99,102,103,107,110]. Lazardis and co-workers [57,104,105,111,115] carried out a number of This article is protected by copyright. All rights reserved.…”
Section: /48supporting
confidence: 69%
See 2 more Smart Citations
“…Similar distortions of β-sheet conformations were reported in other simulations studies of PG-1 in water or in the presence of micelles but were not related to possible issues with the ability of the force field to describe correctly the conformation of the peptide [99,102,103,107,110]. Lazardis and co-workers [57,104,105,111,115] carried out a number of This article is protected by copyright. All rights reserved.…”
Section: /48supporting
confidence: 69%
“…Given the high sequence and structural similarity among β-AMPs, it is likely that the same observations would apply to MD simulations of thantanin, arenicins, tachyplesins, polyphemusins and androctonin. There have been a number of MD simulation studies of β-AMPs and in particular of PG-1 [57,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] (reviewed in [114]). Interestingly, only one of these studies contained a quantitative analysis of β-sheet content.…”
Section: /48mentioning
confidence: 99%
See 1 more Smart Citation
“…After imposition of the β-sheet hydrogen bonds, further equilibration MD was run for 200 ps, followed by minimization. The NOE constraints were removed, and then the individual tetramers and octamers were placed with the more hydrophobic side facing an anionic implicit pore with radius R o = 12 Å and curvature k = 15 Å, the optimal pore geometry for protegrin octamers found in ref . The decamer barrel employed the optimal decameric implicit pore geometry of R o = 16 Å and k = 20 Å .…”
Section: Methodsmentioning
confidence: 99%
“…Pre-formed β-barrels of several similar β-hairpin AMPs in NCNC parallel topology were found to be much less stable than those of protegrin 43 . We also studied protegrin NCNC parallel β-barrels of 6–14 peptides: although the nonamer had the lowest energy, a range of pore sizes 7–13 peptides had relatively consistent favorability 48 . Those results were consistent with the predictions of the solid-state NMR study 25 , which suggested an octamer, but inconsistent with 29 , which suggested a larger pore.…”
Section: Introductionmentioning
confidence: 99%